Law Enforcement Strategy For Violations Of Foreign Citizens' Residence Permits In Gorontalo - Umar, Supriandi; Puluhulawa, Fenty U; Muhtar, Mohamad Hidayat (SM Institute, 2025)
This research seeks to examine the law enforcement approach addressing breaches of stay permits by foreign nationals (WNA) under the jurisdiction of the Class I TPI Gorontalo Immigration Office, as well as to identify the practical challenges encountered. This research primarily examines the coordination challenges across agencies in overseeing and prosecuting foreign nationals who breach visit visas, along with the obstacles faced by immigration agents in managing instances of stay permit abuse. This research employs an empirical legal methodology using a qualitative approach, supplemented by normative data. Data collection was conducted by observation, comprehensive interviews with immigration officers, and the recording of institutional data. The research was conducted in the Class I TPI Gorontalo Immigration Office due to the prevalence of visa abuse cases involving foreign nationals, particularly from Sri Lanka, Vietnam, and China. The study's findings reveal that breaches of stay permits by foreign nationals in Gorontalo predominantly arise from inadequate administrative oversight and a deficiency in both the quantity and expertise of personnel, particularly immigration investigators proficient in foreign languages and capable of executing their duties with professionalism. Furthermore, the cooperation across authorities like the National Police, the Indonesian National Armed Forces, the Ministry of Foreign Affairs, and local governments remains suboptimal, resulting in delayed discovery and management of infractions. Law enforcement via administrative means, including deportation and deterrent, has been implemented; nevertheless, it has proven insufficient without complementary preventative strategies, such as enhancing public legal knowledge and using information technology for oversight. Therefore, a reconfiguration of law enforcement strategies is essential, encompassing the enhancement of institutional capacity, the elevation of human resource quality, and intersectoral collaboration, enabling Indonesia to uphold immigration sovereignty equitably and responsibly in the context of globalization and transnational mobility.